RISK FACTORS FOR IMPLANT LOSS: THE ROLE OF SYSTEMIC DISEASES AND LOCAL CONDITIONS IN THE CONTEXT OF PERIODONTOPATHY. A NARRATIVE REVIEW - Liviu Manole; Maria-Alexandra Martu; Vlad Danila; George-Alexandru Maftei; Luchian Ionut; Mihaela Salceanu; Silvia Martu; Liliana Pasarin (Romanian Dental Association for Education, 2022)
The aim of this review is to provide an overview of the current evidence of some popular food supplements and superfoods that might be of interest in periodontology. Although the number of publications investigating the effect of these products on human health and their possible use in medicine is increasing, only little is known so far regarding their effects on periodontal tissues and their possible use in periodontal treatment or medicine. In summary, an increasing number of studies have revealed aspects and effects of these so-called lifestyle or fitness supplements and superfoods that may have an impact on periodontal health and healing after treatment. However, some the current evidence is of a very low quality, and more validated scientific data are required before their possible use in prevention or treatment of periodontal diseases can be made.